OPTIMALISASI DIGITAL MARKETING DI MASA PANDEMI DI KELURAHAN PANEMBAHAN, KRATON, DIY - Hastho Joko Nur Utomo; Eny Endah Pujiastuti; Rifki Indra Perwira; Heru C. Rustamadji (Dharma: Jurnal Pengabdian Masyarakat, 2021)
Since the covid pandemic entered the DIY area, residents of the community of RW 13, Panembahan Village have been affected. Public opinion decreased. The community service team from UPN veteran Yogyakarta is trying to help overcome this with community empowerment programs through digital business / digital marketing. Continuously and slowly the condition of the people's income can increase again. Promotion through social media is optimized through whatssapp groups, Instagram and market places.